Neonatal and Maternal Outcomes in Pregnant Women With Cardiac Disease. Issue 21 (6th November 2018) - Owens, Amanda; Yang, Jie; Nie, Lizhou; Lima, Fabio; Avila, Cecilia; Stergiopoulos, Kathleen
Abstract : Background: Pregnant women with underlying heart disease (HD) are at increased risk for adverse maternal, obstetric, and neonatal outcomes. Methods and Results: Inpatient maternal delivery admissions and linked neonatal stays for women with cardiomyopathy, adult congenital HD, pulmonary hypertension (PH), and valvular HD were explored utilizing the Statewide Planning and Research Cooperative System (New York), January 1, 2000, through December 31, 2014, with the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) . Maternal major adverse cardiac events, neonatal adverse clinical events (NACE), and obstetric complications were recorded. Outcomes were compared using multiple logistic regression modeling. Among 2 284 044 delivery admissions, 3871 women had HD; 676 (17%) had cardiomyopathy, 1528 (40%) had valvular HD, 1367 (35%) had adult congenital HD, and 300 (8%) had PH. Major adverse cardiac events occurred in 16.1% of women with HD, with most in the cardiomyopathy (45.9%) and PH (25%) groups. NACE was more common in offspring of women with HD (18.4% versus 7.1%), with most in the cardiomyopathy (30.0%) and PH (25.0%) groups. Increased risk of NACE was noted for women with HD (odds ratio [OR]: 2.8; 95% confidence interval [CI], 2.5–3.0), with the highest risk for those with cardiomyopathy (OR: 5.9; 95% CI, 5.0–7.0) and PH (OR: 4.5; 95% CI, 3.4–5.9). Preeclampsia (OR: 5.1; 95% CI, 3.0–8.6), major adverse cardiac events (OR: 2.3; 95% CI, 1.8–2.9), preexisting diabetes mellitus (OR: 4.3; 95% CI, 1.5–12.3), and obstetric complications (OR: 2.9; 95% CI, 1.7–5.2) were independently associated with higher NACE risk. Conclusions: Neonatal complications were higher in offspring of pregnant women with HD, particularly cardiomyopathy and PH. Preeclampsia, major adverse cardiac events, obstetric complications, and preexisting diabetes mellitus were independently associated with a higher risk of NACE.